Geochemistry and petrogenesis of kimberlite intrusions from the eastern lobe the Du Toitspan kimberlite pipe, South Africa - Ramokgaba, Lesego (University of Cape Town, 2021)
The Du Toitspan kimberlite pipe located on the outskirts of Kimberley South Africa, is one four Cretaceous aged major kimberlite pipes from the well-known Kimberley cluster, the type locality for archetypal group I kimberlites. Twenty-seven samples representative of various kimberlite intrusions from the eastern lobe of the Du Toitspan kimberlite pipe have been analysed for their whole-rock geochemistry and mineral chemistry (olivine and phlogopite) with the aim of developing semi-quantitative models that constrain their petrogenesis and characterise their respective source region(s). Investigated intrusions include; D13-phlogopite kimberlite, D14-monticellite kimberlite, D17-serpentinized phlogopite kimberlite, and several narrow (<1m) calcite kimberlite dykes ranging in texture from aphanitic to macrocrystic. The aphanitic calcite dykes were further sub-divided into; a phlogopite-rich calcite kimberlite, a perovskite-rich calcite kimberlite, opaque-rich calcite kimberlites and serpentine calcit e kimberlites.